Molecular characterization of heavy metal-tolerant bacteria and their potential for bioremediation and plant growth promotion - Saira Abbas; Saira Abbas; Sobia Zulfiqar; Muhammad Arshad; Nauman Khalid; Nauman Khalid; Amjad Hussain; Amjad Hussain; Iftikhar Ahmed (Frontiers in Microbiology)
IntroductionHeavy metal pollution adversely affects soil health by disrupting the microbial community structure and functions. The current study aimed to isolate and characterize heavy metal-tolerant bacterial strains and evaluate their potential for soil bioremediation and promoting agricultural sustainability.MethodsA total of 68 bacterial strains were isolated from industrial discharge-contaminated sites and screened for their maximum tolerance limits (MTL) against Cr, Cu, Pb, As, and Cd. The biosorption potential of 23 phylogenetically diverse strains was evaluated. Molecular identification was carried out through 16S rRNA gene sequencing, and plant growth-promoting genes (acdS and nifH) were screened. Four representative strains (NCCP-650T, NCCP-614, NCCP-644, and NCCP-602) were tested for their effect on the growth of Brassica napus under axenic conditions with 50 mg/L of each metal.ResultsSeveral isolates exhibited high MTLs, with tolerance up to 3600 mg/L for Cr, 3300 mg/L for Cu, and 3000 mg/L for Cd and As, while Pb tolerance reached 2100 mg/L. Biosorption was highest for Pb, followed by Cd and Cu; Cr and As were less effectively biosorbed. Molecular identification revealed affiliation of strains to 19 bacterial genera, with Bacillus (21%), Pseudomonas (12%), and Staphylococcus (10%) as dominant. Seven strains harbored both acdS and nifH genes, with 15 and 8 strains positive for nifH and acdS individually. In plant experiments, all four tested strains improved B. napus growth under heavy metal stress, with NCCP-650T showing the most significant enhancement.DiscussionThe isolated strains demonstrated significant tolerance and biosorption of toxic metals, along with plant growth-promoting potential. These findings suggest that selected isolates, particularly NCCP-650T, can serve as bioinoculants for enhancing plant growth and bioremediation in metal-contaminated environments.